2020
DOI: 10.3892/ol.2020.11574
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of immune/stromal-related gene biomarkers in renal cell carcinoma

Abstract: Immune/stromal-associated genes may be promising biomarkers for cancer diagnosis and the determination of clinical cancer treatment options. The aim of the present study was to identify prognostic stromal/immune-associated genes in renal cell carcinoma (RCC). RCC gene expression data (885 cases) were obtained from The Cancer Genome Atlas database. Immune/stromal scores were calculated by using the ESTIMATE package in R. Immune/stromal scores were significantly associated with Tumor-Node-Metastasis stage, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The expression patterns of these genes expressed in the tumor microenvironment provide a powerful indicator of prognosis of patients with RCC. The differences in predictive IRGs identified by Wang et al (42) Our present study may be explained by the former's use of the ESTIMATE package of R to score the immune/stromal of TCGA samples and then to screen differentially expressed genes using the Lasso Cox regression model to build a prognostic six gene-based clinical model to predict the survival of patients with ccRCC. In contrast, here we screened for differentially expressed IRGs acquired from the ImmPort database, and we then identified IRGs related to survival among the differentially expressed genes and used the Lasso Cox regression model to select IRGs with the highest ability to predict prognosis to construct the prognostic model.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The expression patterns of these genes expressed in the tumor microenvironment provide a powerful indicator of prognosis of patients with RCC. The differences in predictive IRGs identified by Wang et al (42) Our present study may be explained by the former's use of the ESTIMATE package of R to score the immune/stromal of TCGA samples and then to screen differentially expressed genes using the Lasso Cox regression model to build a prognostic six gene-based clinical model to predict the survival of patients with ccRCC. In contrast, here we screened for differentially expressed IRGs acquired from the ImmPort database, and we then identified IRGs related to survival among the differentially expressed genes and used the Lasso Cox regression model to select IRGs with the highest ability to predict prognosis to construct the prognostic model.…”
Section: Discussionmentioning
confidence: 92%
“…The difference is that our study is based on ccRCC patients and established a clinical immune gene model to predict the clinical prognosis of ccRCC patients. Another analysis of TGCA RCC data identified a prognostic 6-DEG classifier, including genes encoding IL21R, ATP6V1C2, GBP1, P2RY10, GBP4, and TNNC2 ( 42 ). Further analysis using this model revealed significant associations between immune/stromal scores and clinicopathological staging.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been rapid progress in the research of RCC tumor microenvironments. For instance, one study has revealed the prognostic and predictive value of immune/stromal-related gene biomarkers in renal cell carcinoma 17 . A separate study has con rmed the prognostic value of an immune-associated gene panel for KIRC 18 .…”
Section: Discussionmentioning
confidence: 99%
“…MS4A1 is associated with apoptosis of B-cell lymphoma Ramos cells ( Kawabata et al, 2013 ). P2RY10 has been reported to be a tumor microenvironment-associated gene and a potential diagnostic biomarker of metastatic melanoma ( Wang et al, 2018 , 2020 ). PLA2G2D has been reported to moderate inflammation and could be a potential biomarker for treating inflammatory disorders ( Miki et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%